Making endless war : the Vietnam and Arab-Israeli conflicts in the history of international law - Cuddy, Brian; Kattan, Victor (University of Michigan Press, 2023)
Making Endless War is built on the premise that any attempt to understand how the content and function of the laws of war changed in the second half of the twentieth century should consider two major armed conflicts, fought on opposite edges of Asia, and the legal pathways that link them together across time and space. The Vietnam and Arab-Israeli conflicts have been particularly significant in the shaping and attempted remaking of international law from 1945 right through to the present day. This carefully curated collection of essays by lawyers, historians, philosophers, sociologists, and political geographers of war explores the significance of these two conflicts, including their impact on the politics and culture of the world's most powerful nation, the United States of America. The volume foregrounds attempts to develop legal rationales for the continued waging of war after 1945 by moving beyond explaining the end of war as a legal institution, and toward understanding the attempted institutionalization of endless war.
Keywords: War (International law); World politics -- 20th century.; World politics -- 21st century.; Vietnam War, 1961-1975.; Arab-Israeli conflict.; United States -- Politics and government -- 21st century.; Guerre (Droit international); Politique mondiale -- 20e siècle.; Politique mondiale -- 21e siècle.; Guerre du Viêt-nam, 1961-1975.; Conflit israélo-arabe.; États-Unis -- Politique et gouvernement -- 21e siècle.; LAW / International.; HISTORY / Middle East / Israel & Palestine.; Arab-Israeli conflict; 1961-1975